Job satisfaction in medicine teachers of a peruvian university - Challco-Dávila, Laurie S. (2019)
Introduction: Numerous studies indicate that job satisfaction is a dimension of quality management and that there are factors capable of improving it. On the other hand, it is demonstrated that there is a strong relationship between high job satisfaction and other motivating factors of the worker, such as the organization and management of change, the perception of management or the hierarchical relationship. Method: An observational, descriptive, prospective and cross-sectional study of correlational design was carried out in 60 teachers of the faculty of medicine of the Universidad Nacional Hermilio Valdizán de Huánuco. Results: We found that, in relation to the type of contract, 33 (55%) teachers are hired and 27 (45%) teachers are appointed. Likewise, the total of teachers is not satisfied with the salary they receive for their work as teachers. There is an association between workload and job satisfaction in the faculty of Medicine. Conclusion: There is no association between recognition and job satisfaction in teachers of the Professional School of Human Medicine. There is no evidence of an association between work remuneration and job satisfaction among teachers. There is an association between the workload and job satisfaction in the teachers of the faculty of Medicine of the Universidad Nacional Hermilio Valdizán.